Analisis Proses Bisnis Peningkatan Layanan Sistem Jaringan Dokumentasi dan Infomasi Hukum Kabupaten/Kota di Daerah Provinsi Jawa Barat Menggunakan Metode Umpan Balik 360 - Beny Ruhiman (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2019)
The rapid flow of information, supported by the development of informationtechnology, requires the government to adapt to the current situation. JDIH'srole is not only to document regulations and to publish them, but to make effortsto disseminate legal information to the public. The purpose of this study is toanalyze the Business Process of Service Improvement for District/City LegalDocumentation and Information Network Systems in the Province of West JavaUsing the 360 Feedback Method. 360 Assessment is a method of evaluatingorganizational performance against its employees, self-assessment is carriedout from various directions starting from the top management, middlemanagement, peer (equal) and subordinate (subordinate). The results of thestudy show that the management of JDIH is in accordance with the standardsthat have been set so that it can help to simplify and harmonize regulations soas to avoid overlapping